WEWENANG KOMISI PEMBERANTASAN KORUPSI (KPK) DALAM MELAKUKAN PENCEGAHAN TINDAK PIDANA KORUPSI MELALUI PENDIDIKAN ANTI KORUPSI - Weda Mahendra, IGN; Rai Setiabudhi, I Ketut; Tjatrayasa, I Made (Kertha Wicara : Journal Ilmu Hukum, 2013)
In countries with high levels of corruption, goverment has no any credibility because the goverment has become part of the corruption and cannot be expexted to be aproblem solver expect law enforcement a gainst corruption, the state goverment and law enforcement institutios agencies to be apart of the coruption, it will be ditticult to realize a fair law enforcement in Indonesia. Based on these ideas, the formation of anti-coruption comission based on legislation No 30/2002 abaut anti-corruption commision is very important and promising for efforts to eradicate corruption in Indonesia which is more effective this caused by in accordance with the provision of article 3 legislation No. 30/2002 abaut anti-corruption commision explicitly : ”anti-Corruption commision is a state agency in carrying out its duites and authorites are independent and free from the influence of any power the explanation code of anti-corruption commision No. 30/2002.
Keywords: Corruption, anti-Corruption Commisions, and the Prevention and Combating of Corruption